KARAKTERISASI SENYAWA ANALGETIKA-ANTIINFLAMASI N-(4t-BUTILBENZOIL)-p-AMINOFENOL YANG DISINTISES DENGAN KATALIS ASAM - Hadi Barru Hakam Fajar Siddiq, Dewi Rashati, Farida Suryaningsih (AKADEMI FARMASI JEMBER, 2017)
The N-(4t-Butylbenzoyl)-p-Aminophenol compound was a synthesis compound between p-aminophenol and 4t-Butylbenzoyl chloride by using H2SO4 catalyst. The addition of H2SO4 catalyst purposed to accelerate the rate of rection in the synthesis of the compound and increased yield of product. The N-(4t-Butylbenzoil)-p-Aminophenol compound is beneficial as an antiinflammatory analgesic. This research were proposed to determine characteristics of the anti-inflammatory analgesic synthesis of N-(4t-Butylbenzoyl)-p-Aminophenol compound by using H2SO4 catalyst. Characterization conducted in this research were physical and chemical characterization. The physical characterization were organoleptic test, crystal form test and melting point test. While chemical characterization were UV-Vis spectrophotometry and FTIR. Result of organoleptic test showed sample had powder form, white-gray colour and not taste. Melting point of N-(4t-Butylbenzoyl)-p-Aminophenol compound was 193.33 °C. The optimum wavelength of UV-Vis spectrophotometry got 2 peaks at the wavelengths 290 and 295 nm. The result of FTIR showed that N-(4t-Butylbenzoyl)-p-Aminophenol compound had peaks.Keywords: N-(4t-butyl benzoil)-p-aminophenol, catalyst